Предмет: Алгебра,
автор: Marrkuri
Упростите выражение (2х-1)(х+5) и найдите его значение при х= -2
Помогите,пожалуйста.
Ответы
Автор ответа:
0
( 2х - 1 )( Х + 5 ) = 2х^2 + 10х - Х - 5 = 2х^2 + 9х - 5
Х = - 2
2( - 2 )^2 + 9•( - 2 ) - 5 = 8 - 18 - 5 = - 15
Х = - 2
2( - 2 )^2 + 9•( - 2 ) - 5 = 8 - 18 - 5 = - 15
Автор ответа:
0
2х^2+9х-5
8-18-5=-15
Ответ:-15
8-18-5=-15
Ответ:-15
Похожие вопросы
Предмет: Қазақ тiлi,
автор: bulyganikita7
Предмет: Математика,
автор: Аноним
Предмет: Информатика,
автор: nurmakhanoverdaulet
Предмет: История,
автор: Polina8656
Предмет: Биология,
автор: VickaIvanova2004